Lifesaving surgical approaches for severe penetrating knife injury to the neck - Anand Shankar Soundararajan; Kesava Phani Krishna (Journal of Cardiothoracic Surgery)
Abstract Background Penetrating neck injuries are rare and require urgent surgical intervention to prevent life-threatening complications. This report highlights a unique case involving complex surgical repair of tracheal, esophageal, and vascular injuries following a homicidal assault, emphasizing the challenges and techniques used in managing such severe trauma. Case presentation A 45-year-old female presented with a severe penetrating neck injury after an alleged homicidal assault with a knife. The patient was in hypovolemic shock and required immediate resuscitation. Endotracheal intubation was performed through the transected tracheal segment, followed by surgical exploration in the operating room. Findings included partial transection of the carotid sheath, complete transection of the trachea, and oesophagus. Surgical repair involved using lateral polypropylene 5-O sutures for the carotid sheath, end-to-end oesophageal repair with absorbable 3 − 0 polygalactin sutures. As tracheal repair was not possible posterior wall was approximated with 3 − 0 polypropylene and size 7 tracheostomy tube was inserted and secured. The patient was managed post-operatively in the ICU and was discharged in stable condition on the 25th day adviced regular follow-up. This case underscores the importance of prompt airway management and surgical intervention in penetrating neck injuries. The meticulous repair of all injured structures and diligent post-operative care are crucial to a successful outcome. This report contributes to the limited literature on managing complex penetrating stab injuries to the neck and highlights the importance of a multidisciplinary approach in such cases.